Morally obliged to caring? Rethinking inclusivity through relational ethics in place branding - Cassinger, Cecilia ; 0000-0002-0052-4045; Ripoll Gonzales, Laura; Porzionato, Monica (International Place Branding Association Conference, Manchester, United Kingdom, 2025-10-29 - 2025-10-31, 2025)
This paper contributes to ongoing debates on inclusive place branding by introducing a feminist ethics of care approach. While existing research often treats inclusion as a strategic or instrumental move, aimed at enhancing collaboration or democratic legitimacy, it is rarely framed as an ethical imperative. Moreover, prevailing human-centred perspectives tend to marginalize non-human and environmental dimensions of place. In response, we argue for a relational and performative understanding of place branding, one that is essential for advancing genuinely inclusive practices. Theoretical Framework We outline a feminist ethics of care approach that shifts the focus from conventional stakeholder engagement toward relationality, interdependence, and vulnerability, encompassing human, non-human, and environmental dimensions of place. This perspective conceptualizes places as dynamic and relational, where agency is distributed across human actors, non-human entities, and ecological processes. Main Research Approach A qualitative study of residents’ experiences with sustainable transition in a rural Spanish region serves as an illustrative example to explore how theories on feminist ethics of care could inform future research in place branding. Key Arguments/Findings Our analysis shows how a care-oriented approach can shape place identity and support more equitable and just branding practices. It offers an alternative to commodification by foregrounding the moral responsibilities of stakeholders to nurture communities and environments. Conclusions We argue that inclusivity should be embedded at the core of place branding practices. A care ethics approach offers transformative potential by reframing branding as a moral practice grounded in social justice and environmental sustainability. In doing so, it moves inclusion beyond tokenism, fostering deeper, more meaningful engagement with the human, non-human, and environmental dimensions of place. Practical Implications This approach encourages place brand practitioners and policymakers to rethink inclusivity as an ongoing ethical responsibility. It invites the adoption of practices that nurture long-term, reciprocal relationships with place, understood as a network of human, non-human and environmental connections, enabling more meaningful and sustainable branding strategies.
Keywords: Care; ethics; regions; place; communication